Antonio J. GIL GONZÁLEZ y Pedro Javier PARDO, eds., "Adaptación 2.0. Estudios comparados de intermedialidad. In honorem José Antonio Pérez Bowie". Binges, Orbis Tertius, 2018, 300 pp. - Blesa, Túa; Pueo, Juan Carlos (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Review of Antonio J. GIL GONZÁLEZ y Pedro Javier PARDO, eds., Adaptación 2.0. Estudios comparados de intermedialidad. In honorem José Antonio Pérez Bowie. Binges, Orbis Tertius, 2018, 300 pp.
Keywords: Adaptación 2.0. Estudios comparados de intermedialidad. In honorem José Antonio Pérez Bowie